PENGARUH LINGKUNGAN KERJA FISIK, EFIKASI DIRI, DAN PENGEMBANGAN KARIER TERHADAP KEPUASAN KERJA KARYAWAN SUKU DINAS TENAGA KERJA, TRANSMIGRASI, DAN ENERGI KOTA ADMINISTRASI JAKARTA UTARA - Adzqia Zahradiva Khanza Syavira (2022)
This research is a quantitative study that aims to determine the effect of the physical work environment, self-efficacy, and career development on job satisfaction of employees of the North Jakarta City Administration of Manpower, Transmigration and Energy Sub-agency. This study used 38 respondents with permanent employee positions in the North Jakarta Administrative City Office of Manpower, Transmigration and Energy. Data collection was carried out through distributing questionnaires. The data analysis technique used is Partial Least Square (PLS) statistics, namely SmartPLS 4.0 through partial (T) and simultaneous (F) hypothesis testing. The results are (1) the physical work environment has a positive and significant effect on employee job satisfaction, (2) self-efficacy has a positive and significant effect on employee job satisfaction, (3) career development has a positive and significant effect on employee job satisfaction, and (4) the environment physical work, self-efficacy, and career development have a significant influence on the job satisfaction of employees at the North Jakarta Administrative City Manpower, Transmigration and Energy Sub-agency.